1974
DOI: 10.1139/v74-536
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Implications from the Conformational Analysis of the Seven-membered Ring in 5-Oxabenzocycloheptene

Abstract: LOUIS CANUEL and MAURICE ST-JACQUES. Can. J. Chem. 52, 3581 (1974). The computer analysis (LAOCN-3 program) of the p.m.r. spectrum of 5-oxabenzocycloheptene (3) at -105' has provided values for all coupling constants about the C3-C4 bond, while the complete line-shape simulation (DNMR program) has provided the following activation parameters: AG* = 9.5 kcal/rnol (at -57"), AH' = 9.9 kcal~mol, and AS* = 1.5 e.u. A novcl long distance (transannular) deuterium isotope effect has been discovered during the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The substitution of C-5 by an oxygen atom in 5-oxabenzocycloheptene (9) lowers the energy barrier to 9.5 kcal/mol (13). Furthermore, the presence of two oxygen atoms in the ring reduces the value to 7.9 kcal/mol for 2 and to 6.5 kcal/mol for 1,5-dioxa-6,7-benzocycloheptene (14) (8,24).…”
Section: Dynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of C-5 by an oxygen atom in 5-oxabenzocycloheptene (9) lowers the energy barrier to 9.5 kcal/mol (13). Furthermore, the presence of two oxygen atoms in the ring reduces the value to 7.9 kcal/mol for 2 and to 6.5 kcal/mol for 1,5-dioxa-6,7-benzocycloheptene (14) (8,24).…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…After 8 h, most of the starting material had disappeared (less -30%); compounds 8c and 8e were then isolated and purified from the crude mixture by vpc under the conditions given above. Each product was characterized by 'H and 13 C spectra (Tables 1 and 2) …”
Section: 2-mentioning
confidence: 99%
“…Our results seem to show that the same trend exists in seven-membered rings. A previous report (13) has shown that while A6 for the benzylic methylene protons is -0.106ppm in benzocycloheptene, introduction of a p oxygen atom moves the equatorial proton at 0.504ppm upfield from the axial proton. Assuming that the same trend applies qualitatively to 2 (or 6) we would expect the two oxygens P to the protons on C-3 to shift the equatorial proton at about 0.4 ppm upfield from the axial proton since in benzocycloheptene A6 for the corresponding protons in 0.41 ppm (14).…”
Section: Conformations Of the Seven-membered Ringsmentioning
confidence: 84%
“…It is important to point out that each of the compounds prepared actually contains essentially equal amounts of syn and anti isomers, but because the 'Hmr signals of each side of the ring are essentially independent (14,16), only the anti isomers have been shown in the schemes.…”
Section: D(h)mentioning
confidence: 99%
“…The key reaction involved a catalytic reduction of double bonds with deuterium gas; it is expected to place vicinal deuterium atoms in a predoniinalltly cis arrangement (14,16). As these compounds were prepared at different times, the isotopic purity varied according to the experimental conditions.…”
mentioning
confidence: 99%